Solid-acid-based process for the conversion of hemicellulose - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (Green Chemistry, 2010)
We describe a solid-acid-catalyzed conversion of hemicellulose (a component of lignocellulosic material) into xylose, arabinose and furfural in aqueous media.

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation